Causes and countermeasures of difficulties in PICC insertion under ultrasound guidance (超声引导下经外周静脉置入中心静脉导管送管困难的原因分析及对策) - GU Lin (谷林) (Journal of International Translational Medicine Limited, 2024)
A peripherally inserted central catheter (PICC) can provide long-term and safe intravenous access for cancer patients with chemotherapy and patients who need long-term infusion and parenteral nutrition. This paper reviews studies on causes and countermeasures of difficulties in PICC insertion under ultrasound guidance. Common actors influencing the PICC insertion includes vascular access selection, vasospasm, puncture position, puncture operator and so on. Targeted nursing interventions should be carried out to prevention risk factors and improve the success rate of PICC placement, therefore reducing the pain of patient during PICC insertion under ultrasound guidance. (经外周静脉置入中心静脉导管(PICC)具有安全、可靠、留置时间长、并发症少等优点, 在临床上得到了广泛应用, 特别适用于肿瘤化疗患者及需要长期输液、静脉高营养治疗的患者。本文对PICC置管过程中送管困难的原因及处理对策进行综述, PICC置管过程中送管困难的原因通常包括血管选择、血管痉挛、穿刺体位、操作者因素等, 护理人员应针对相关的因素开展预防及实施高效处理方法, 提高PICC置管的成功率, 减轻患者痛苦。)